Strengthening The Authority Of The Indonesian Ombudsman In The Public Service Sector - Saut Parulian Panjaitan (Universitas Sriwijaya, 2022)
In the era of disruption, because of advances in communication and information technology, causing disruptions in the administration of government, which was originally based on the monopoly and power paradigm, became a public service paradigm based on the principle of good governance through e-government services. In carrying out the task of supervising public services, until now the authority of the Indonesian Ombudsman is still very limited, which can be seen from legal products in the form of recommendations that do not have legal coercion for state/government administrators who commit maladministration. On that basis, the Indonesian Ombudsman issues a regulation on the Indonesian Ombudsman which authorizes its decisions, which are final and binding, in public service disputes through an adjudication process. In fact, the position of the Indonesian Ombudsman should indeed be as an institution that only gives influence (magistratur of influence) to state/government officials in order to respect the rights of citizens in public services. To strengthen the authority of the Indonesian Ombudsman, it is carried out (a) strengthening the constitutional position of the Indonesian Ombusman, (b) clarifying the scope of supervision by the Ombudsman, both regarding what things can be monitored and to whom the supervision can be carried out, (c) formulating threats sanctions for public service officials who do not implement the Ombudsman's recommendations in reports of violations of public services, (d) formulate the Ombudsman's authority that is active-preventive, and (e) formulate coercive power against the Ombudsman's recommendations as an effort to improve the quality of public services.